ANALISA PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI ENERGI PENGGERAK POMPA MINYAK PADA STASIUN PENGISIAN BAHAN BAKAR UMUM DI KOTA DENPASAR - I Putu Juliawan; I Nyoman Setiawan; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2022)
Utilization of renewable energy as a source of electrical energy is an environmentallyfriendly energy development, one of which is the use of solar energy by developing solar PV onthe roof of buildings as a medium for installing solar modules. In this study, a rooftop solar PVplan was carried out at the Nangka Utara gas station as a source of electrical energy whichaims to reduce the cost of PLN electricity bills. The rooftop solar PV system at the Nangka Utaragas station uses an On-grid solar PV system without batteries, using 36 units of 415 Wpmonocrystalline solar modules and one 15kW inverter unit. Planning for rooftop solar PV of theNangka Utara gas station with a capacity of 14.9 kWp with the resulting energy production of20.43 MWh per year. The initial investment cost required is IDR. 101.179,000 with a paybackperiod of 5 years and 8 months.